Code Thumbnails: Using Spatial Memory to Navigate Source Code - DeLIne, Robert; Czerwinski, Mary; Meyers, Brian; Venolia, Gina; Drucker, Steven; Robertson, George (VLHCC '06: Proceedings of the Visual Languages and Human-Centric Computing, 2006)
Modern development environments provide many features for navigating source code, yet recent studies show the developers still spend a tremendous amount of time just navigating. Since existing navigation features rely heavily on memorizing symbol names, we present a new design, called Code Thumbnails, intended to allow a developer to navigate source code by forming a spatial memory of it. To aid intra-file navigation, we add a thumbnail image of the file to the scrollbar, which makes any part of the file one click away. To aid interfile navigation, we provide a desktop of file thumbnail images, which make any part of any file one click away. We did a formative evaluation of the design with eleven experienced developers and present the results.